Conjugation of Small Molecules to RNA Using a Reducible Disulfide Linker Attached at the 2′‐OH Position through a Carbamate Function. Issue 33 (19th August 2019) - Gauthier, Florian; Malher, Astrid; Vasseur, Jean‐Jacques; Dupouy, Christelle; Debart, Françoise
Abstract : A post‐synthesis conjugation method was developed to functionalize oligoribonucleotides with various small molecules of biological interest using a reduction‐sensitive disulfide linker connected to 2′OH via a carbamate function. For this, first we prepared a 2′‐ O ‐[( N ‐(acetylthio)‐ethylcarbamoyl] (2′‐ O ‐AcSEC) uridine phosphoramidite as the key precursor of the disulfide linker, that was incorporated into 21‐mer RNAs. Next the 2′‐ O ‐AcSEC group was converted on solid support to the activated 2′‐ O ‐[ N ‐(2‐pyridyldisulfanyl)‐ethylcarbamoyl] (2′‐ O ‐PySSEC) group. Finally, the coupling between 2′‐ O ‐PySSEC‐modified RNA and diverse small molecules bearing a thiol function was based on a thiol‐disulfide exchange reaction in solution. Several RNA‐small molecule conjugates were obtained with satisfactory conjugation yields. An RNA was successfully double‐conjugated with an anticancer drug (doxorubicin) attesting the efficiency and the robustness of the conjugation method. We have shown that the disulfide‐linked RNA‐small molecule conjugates were cleaved upon 5.6 mm glutathione treatment, featuring the release of the small molecules in cells. Abstract : In this paper, we developed a post‐synthesis conjugation of small molecules to RNA using a reduction sensitive disulfide linker connected to 2′OH through a carbamate function.